Gm614 Protects Germinal Center B Cells From Death by Suppressing Caspase-1 Transcription in Lupus-Prone Mice - He, Youdi; Xu, Ruonan; Zhai, Bing; Zhou, Shan; Wang, Xiaoqian; Wang, Renxi (Frontiers in Immunology, 2020)
Only a few signaling pathways were reported in the germinal center (GC) B-cell proliferation and death. In this study, we showed that a novel uncharacterized Gm614 was highly expressed in GC B cells from lupus-prone mice. Critically, GC B-cell-specific ablation of Gm614 promoted GC B-cell death to mitigate autoimmune symptoms, whereas B-cell-specific Gm614 overexpression protected GC B cells from death to exacerbate autoimmune symptoms. Mechanistically, nuclear-localized Gm614 reduced caspase-1 expression in GC B cells by binding with caspase-1 promoter to suppress its activation. Altogether, our results suggest that Gm614 protects GC B cells from death by suppressing caspase-1 transcription in autoimmune diseases. This may provide some hints for targeting cell proliferation involved in autoimmune diseases.